Defining the key elements of the Affolter Model® in a multiprofessional Delphi study: a first step toward evidence-based Tactual Interaction Therapy - Schlunegger, Tamarith; Augstein, Sabine; Munch, Laurent; Roelandt, Frank; Jakobsen, Daniela (Frontiers in Rehabilitation Sciences, 2025)
BackgroundDespite the versatile application of the Affolter Model®, using Tactual Interaction Therapy as a treatment approach in health, social and educational care of people with congenital brain disorder or acquired brain injury, high quality studies with robust designs for efficacy are scarce. Evaluation of the effectiveness of the Tactual Interaction Therapy requires agreement and consensus among practitioners of what constitutes this approach. Such consensus has yet to be achieved.GoalTo map the Affolter Model® by reaching consensus on its core domains among experienced practitioners.MethodsFrom September to December 2022, a modified online Delphi process with four survey rounds was conducted to map the core domains of the Affolter Model®. An international, interdisciplinary project group consisting of four senior instructors, trained in the use of the Affolter Model® created 29 initial statements. In the course of the four survey rounds, 40 practitioners (expert panel), all experienced users of the Affolter Model®, rated these statements on a five-point Likert scale. In addition, new statements were developed as well as new versions of existing statements. These were integrated into the surveys and submitted for evaluation. An a-priory consensus was set at a percentage approval of at least 80%.ResultsThirty-six statements out of a total of 38 statements reached consensus. The majority of statements (29/36) achieved an agreement of more than 90%. Statements that were initially rejected achieved consensus after being rephrased.ConclusionThirty-six core statements describing the Affolter Model® achieved consensus. By mapping the core domains of the Affolter Model®, this study provides a basis for teaching and developing the Affolter Model® in theory and practice and for further research projects to investigate its effectiveness in persons with perceptive and cognitive problems, limiting participation in everyday life.